OPTIMALISASI SUMBER DAYA LALU LINTAS PENERBANGAN: STUDI KASUS TERHADAP KINERJA PEMANDU LALU LINTAS PENERBANGAN - Nabila Angie Istiqomah; Muhammad Riziq Khasani; Dhian Supardam; Lina Rosmayanti (SKY EAST: Education of Aviation Science and Technology, 2026)
Optimizing Human Resources for Air Traffic Control (ATC) is crucial for maintaining the safety and smooth flow of flight operations in Indonesia. This study presents a critical review of air traffic controller performance, focusing on three main pillars: workload, quality of training, and psychological well-being. The research aims to analyze the role of human factors in aviation safety by examining aspects of competency, communication, decision-making, work fatigue, and safety culture within the operational environment. The research methodology utilizes a literature study from various sources such as accident investigation reports, international aviation regulations, and results from previous empirical studies on controller stress and workload, as well as international guidelines related to human factors in ATC. The analysis combines literature review, comparison of training policies, and synthesis of field research findings to identify competency gaps, weaknesses in training programs, and the impact of workload on controller performance and quality of life. The results indicate that a mismatch between the training curriculum and operational demands, as well as high mental workload without adequate stress management compensation, is significantly related to a decline in performance and an increase in safety risks. This article recommends an integrated policy package: revision of curriculum standards based on real-world tasks, increased frequency and quality of simulation training, a workload and mental health management program, and strengthening performance monitoring mechanisms based on safety indicators. The implementation of these recommendations is expected to enhance the readiness of ATC human resources and minimize potential disruptions to flight safety.